ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA PELAKU UMKM JAMU GENDONG DI NGUTER - Wati, Dewi Kusuma; Ismunawan, Ismunawan (JURNAL ILMIAH EDUNOMIKA, 2024)
This study is targeted at examining factors that influence accounting information systems using variables of business scale, length of business, accounting knowledge & use of technology. This study had a population of 72 businesses and the sampling method used a saturated sample. In order to collect the data, a questionnaire was also used, a multiple linear regression model using SPSS media. The results of the study show that business scale & use of technology have a significant impact on the accounting information system for herbal medicine MSMEs in Nguter. However, accounting knowledge & length of business are not significant in the accounting information system for herbal medicine MSMEs in Nguter. Keywords: MSMEs, business scale, length of business, accounting knowledge, use of technology, accounting information systems